The Supreme Court as an electoral issue: evidence from three studies. Issue 1 (2nd January 2022) - Badas, Alex; Simas, Elizabeth
Abstract: Judicial nominations, particularly those to the Supreme Court, have been a salient topic in recent presidential and senate elections. However, there has been little research to determine whether judicial nominations motivate political behavior. Across three studies we demonstrate the important role judicial nominations play in influencing political behavior. In Study 1, we analyze the extent to which voters perceive judicial nominations as an important electoral issue. We find that Republicans—and especially strong Republicans—are more likely to perceive judicial nominations as important. In Study 2, we analyze how congruence with an incumbent Senator's judicial confirmation votes influences voters' decision to vote for the incumbent. We find that congruence with a Senator's judicial confirmation votes is a strong predictor of vote choice. Finally, in Study 3, we analyze data from an original conjoint experiment aimed at simulating a Senate primary election where voters must select among co-partisans. We find that Republican subjects are more likely to select a primary candidate who prioritizes confirming conservative Supreme Court nominees. Among Democratic subjects, however, we find that Democratic candidates who prioritize the Court might actually suffer negative electoral consequences. Overall, our results demonstrate the importance of judicial nominations as an electoral issue.